SAKRALISASI TARI TELEK DALAM UPACARA PIODALAN DI PURA DALEM, DESA ADAT PANJER DENPASAR SELATAN - Ida Ayu Gede Prayitna Dewi -; Anak Agung dwi Dirgantini -; I Komang Dedi Diana -; Ni Wayan Darmayanti - (WIDYANATYA, 2023)
ABSTRACT Telek dance is a type of sacred dance which is always performed during the piodalan ceremony at the village temple which is held in the Panjer Indigenous village, South Denpasar. Research was carried out to answer the problem formulation which consists of: 1) How is the sacredness of the Telek dance in the piodalan ceremony at the Dalem Temple , Panjer Traditional Village, South Denpasar? 2) What is the function of the Telek Dance performance in the Piodalan Ceremony at Dealem Temple, Panjer Traditional Village, South Denpasar? 3) What educational values do Hindu religious dance arts contain in the form of the Telek Dance Performance in the Piodalan Ceremony at Pura Dalem, Panjer Traditional Village, South Denpasar? There are 4 theories used in this research, namely: (1) Religious Theory, (2) Structural Functional Theory, (3) Behavioristic Theory. Based on this analysis, the following conclusions were obtained in the research results: 1). Sacredization of Telek Dance 2). The function of Telek Dance Performance is: a). Functions of Bebali Dance. b). Religious Function. i). Cultural Preservation Function. j). Documentation 3). The educational value of Hindu religious dance contained in the form of the Telek dance performance in the Piodalan ceremony at Pura Dalem, Panjer Traditional Village, South Denpasar is: a). The Value of Sacred Education. b). Hindu Aesthetic Values c). The Value of Ethics and Moral Education Keywords: Sacralization, Telek Dance, Piodalan Ceremony